PENGARUH KEMAMPUAN KOMUNIKASI ORANG TUA TERHADAP KEMAMPUAN BERBICARA ANAK USIA 4-5 TAHUN DI KELURAHAN TUAH KARYA PEKANBARU - Fetmi Putri Permata Putri Permata Permata; Zulkifli '; Nurlita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The background of this research problem is often a child feel embarrassed and pull away when talking with teachers and friends. There are children that are less able to answer questions put to him, there that difficult to express why they like to something, and there they want to tell but have not given the opportunity. Most parents are included in the communication patterns that are less effective. Therefore, the necessary communication skills to assist children in learning to master effective communication and develop a child's ability to speak. The purpose of this study is to determine how much influence the communication ability of parents of children aged 4-5 years in the Kelurahan Tuah Karya Pekanbaru . The study population was all children aged 4-5 years that were in the Kelurahan Tuah Karya Pekanbaru totaling 130 people. The sample used by 56 people. The data collection techniques used were interviews and observation. The data analysis technique used is the formula Pearson Product Moment and analysis of statistical methods Pearson Product Moment Correlation with SPSS 16. From the results obtained there is a strong influence, positive, and significant between parent communication skills with the ability to speak of children aged 4-5 years in the Kelurahan Tuah Karya Pekanbaru . It can be seen from the strong categorized rxy 0.601, t count of 5.5 and 2.00 to 5.5 ttable> 2.00 then it means that there is a positive and significant influence between communication skills with the ability to speak. The resulting determinant coefficient is equal to r2 = 36, it can be seen that the communication skills of parents to give effect by 36% against the speech of children aged 4-5 years in the Kelurahan Tuah Karya Pekanbaru . Keywords: communication skills, the ability to speak